Effect of UV-C Postharvest Disinfection on the Quality of Fresh-Cut 'Tommy Atkins' Mango - Alba Mery Garzón-García; Saúl Ruiz-Cruz; Saúl Dussán-Sarria; José Igor Hleap-Zapata; Enrique Márquez-Ríos; Carmen Lizette Del-Toro-Sánchez; José Agustín Tapia-Hernández; Dalila Fernanda Canizales-Rodríguez; Víctor Manuel Ocaño-Higuera (Polish Journal of Food and Nutrition Sciences)
Mango cv. ‘Tommy Atkins’ is a highly appreciated fruit for its organoleptic characteristics and its resistance to minimal processing. However, some operations as peeling and cutting can generate microbial contamination and loss of bioactive compounds. Ultraviolet short wave (UV-C) is an alternative technology for fresh-cut products that leads to microbial inactivation and the increase of beneficial compounds. The effect of a UV-C dose of 6 kJ/m2 was evaluated on quality attributes of fresh-cut 'Tommy Atkins' mango during days 0, 3, 6, 9, and 12 of storage (5°C, relative humidity: 85-90%), and compared with a positive control (conventional method by immersion in 10 mg/L sodium hypochlorite solution) and a negative control (without treatment). Physicochemical analysis (titratable acidity, pH, total soluble solid content, and firmness), superficial color evaluation, determinations of microbial counts, contents of total carotenoids, phenolics and flavonoids, and antioxidant capacity assays were performed. The results showed that UV-C treatment allowed to preserve microbial safety and superficial color of stored fresh-cut mango, and to increase the content of total carotenoids, which was 19.34 and 26.50 mg β-carotene/100 g fresh weight (FW) for control and UV-C treated sample at day 12 of storage, respectively. The DPPH• scavenging activity of the UV-C treated mango was also higher (0.60 mM TE/g FW) compared to control (0.27 mM TE/g FW) at the end of storage. However, UV-C treatment caused loss of firmness. Some native microorganisms of mango adapted to the stress caused by the treatments and the storage.